Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/cid/cix588
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome Associated With Zika Virus Infection in Martinique in 2016: A Prospective Study

Abstract: ZIKV infection is usually benign, when symptomatic, but in countries at risk of ZIKV epidemics, adequate intensive care bed capacity is required for management of severe GBS cases. Arbovirus RNA detection by RT-PCR should be part of the management of GBS cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…These results support previous findings indicating an association between arboviruses and neuropathies in Brazil during the Zika virus epidemic . The rates of rash, facial paralysis, and paraparesis in patients with GBS in Metropolitan Area II are similar to those previously reported for GBS cases in Latin America and the Caribbean . Our classification of the cause of inflammatory polyneuropathies was based on signs and symptoms reported by the patient and investigated by physicians.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results support previous findings indicating an association between arboviruses and neuropathies in Brazil during the Zika virus epidemic . The rates of rash, facial paralysis, and paraparesis in patients with GBS in Metropolitan Area II are similar to those previously reported for GBS cases in Latin America and the Caribbean . Our classification of the cause of inflammatory polyneuropathies was based on signs and symptoms reported by the patient and investigated by physicians.…”
Section: Discussionsupporting
confidence: 90%
“…Treatment involves plasma exchange or intravenous immunoglobulin. Although the most frequent causes of GBS are Campylobacter jejuni , Cytomegalovirus , and influenza A, the disorder has also been associated with dengue virus and Zika virus . During the Zika virus epidemic in Rio de Janeiro, Brazil, during the period 2015–2016, it was shown that neuropathies increased .…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed 135 full-text articles, of which 31 were eligible for inclusion ( Fig 1). Of the 31 studies, 28 reported countryspecific GBS rates from 13 LAC countries (Tables 1 & 2), 3 regional rates, [18,35,36] 15 background rates [18,[35][36][37][38][39][40][41][42][43][44][45][46][47][48], 11 rates during an arboviral outbreak [49][50][51][52][53][54][55][56][57][58][59], and 5 compared rates before and during an outbreak [27,[60][61][62][63]. Many studies presented data from Brazil (29%) and Colombia (16%), and the majority (68%) were published in 2015 or later.…”
Section: Resultsmentioning
confidence: 99%
“…GBS comprises an acute inflammatory demyelinating polyneuropathy of global incidence, in which about two-thirds of cases occur after bacterial (e.g. Campylobacter jejuni) (Heikema et al, 2015) or viral infection (Oehler et al, 2015), such as by Dengue- (Simon et al, 2016), West Nile- (Leis and Stokic, 2012), Influenza- (Choi and Yeon, 2016), Cytomegalo- (Steger et al, 2012), Human Immunodeficiency- (Girgin et al, 2014), Epstein-Barr (Phillips, 1973;Kim et al, 2016) and Zika viruses (Rozé et al, 2017).…”
Section: Atypicalmentioning
confidence: 99%